Stages and Characteristics of the Formation of the Ownership System in Uzbekistan - Yakubov Ikram Rakhmat ugli (Journal of Learning on History and Social Sciences, 2024)
In this article, the privatization of state property, which is considered an important part of the country's economic development, is carried out in the conditions of Uzbekistan and its results are analyzed based on scientific literature and statistical data.